AI-Driven Customization in Financial Services: Implications for Social Innovation in Nepal - Khadka, Srijana; Rai, Bharat; Khadka, Ajaya Kumar (NCC Journal, 2023)
The study examines the association and influence of Artificial intelligence (AI) adoption and social innovation on decision-making within the Nepalese banking sector. A descriptive and causal-comparative research design is employed in the study. With a purposive sampling design, the study used 230 respondents from commercial banks in Nepal. The study findings show that AI technologies (β = 0.205) and social innovation (β = 0.395) significantly contribute to decision-making (|p < 0.05|). The study scrutinizes specific approaches for fostering social innovation by implementing AI-driven decision-making. Findings revealed meaningful associations between AI, social innovation, and decision-making, emphasizing the interconnected nature of these elements. The study identifies actionable strategies for leveraging AI to promote social innovation. The research implications extend to strategic management, urging financial institutions to integrate AI technologies strategically, aligning technological advancements with societal needs, and fostering a holistic approach to responsible AI adoption. This study contributes valuable insights to the evolving discourse on AI in financial services, providing a nuanced understanding of its implications for decision-making and social innovation within the unique context of Nepalese commercial banks.